2017
DOI: 10.1038/bmt.2017.208
|View full text |Cite
|
Sign up to set email alerts
|

High-dose BCNU/Melphalan conditioning regimen before autologous stem cell transplantation in newly diagnosed multiple myeloma

Abstract: Single-agent high-dose melphalan (HDM, 200 mg/m) has been the most commonly used conditioning regimen prior to autologous stem cell transplant, since its introduction in 1992. We used a more aggressive alkylator-based conditioning regimen in an attempt to overcome early relapse and combat drug resistance. We present a retrospective comparison and long-term follow-up of newly diagnosed patients with multiple myeloma (MM) treated with induction followed by either high-dose carmustine (BCNU) and HDM, or HDM alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…Costa et al [32] recently showed in a Phase I-II trial that the combination of carfilzomib on days -3 and -2 with Mel200 on day -2 is also very active in high-risk patients with relapsed MM receiving SAT, with a 1year PFS of 67% and a 1-year OS of 88%. Other regimens have evaluated various combinations of cytotoxic agents [33][34][35][36] (NCT03687125), immunomodulatory agents [37], proteasome inhibitors [38], and total marrow irradiation [39] with varying success [40]. Despite the promise of an intensified approach in the upfront setting, this is still not routinely used in the relapsed or upfront setting.…”
Section: Improving Outcomes: Conditioning Regimens Post-transplantatmentioning
confidence: 99%
“…Costa et al [32] recently showed in a Phase I-II trial that the combination of carfilzomib on days -3 and -2 with Mel200 on day -2 is also very active in high-risk patients with relapsed MM receiving SAT, with a 1year PFS of 67% and a 1-year OS of 88%. Other regimens have evaluated various combinations of cytotoxic agents [33][34][35][36] (NCT03687125), immunomodulatory agents [37], proteasome inhibitors [38], and total marrow irradiation [39] with varying success [40]. Despite the promise of an intensified approach in the upfront setting, this is still not routinely used in the relapsed or upfront setting.…”
Section: Improving Outcomes: Conditioning Regimens Post-transplantatmentioning
confidence: 99%
“…Melphalan is the standard chemotherapeutic agent that is used in the conditioning therapy prior to autologous HSCT in MM. The dose ranges between 140 and 200 mg/m 2 , given intravenously (IV) [79,81,82,93]. It is cleared from plasma and urine in 1 and 6 hours, respectively.…”
Section: Cryopreservation Versus Noncryopreservation Of Stem Cellsmentioning
confidence: 99%
“…Recently, other drugs have been used in the conditioning therapy prior to autologous HSCT in MM either alone or in combination with HD melphalan [94][95][96][97]. Compared to HD melphalan, the use of ixazomib, BCNU, bortezomib and IV busulfan either alone or in various combinations with HD melphalan in the conditioning therapies has increased the overall response rates and the median OS without additional toxicity [93][94][95][96][97].…”
Section: Cryopreservation Versus Noncryopreservation Of Stem Cellsmentioning
confidence: 99%
“…One exception may be Bendamustine, but this has not been fully explored yet [4]. Several other agents like idarubicin, etoposide, busulfan, carmustine and bortezomib were also studied as a substitute for melphalan, while none of them was shown to be superior [5], some were even more toxic than melphalan alone [6,7], and recent studies comparing melphalan and carmustine did not show any diff erence in terms of TRM [8,9]. Furthermore, there is no universal consensus, when it comes to choice of the treatment modalities.…”
Section: Autologous Transplant An Old Work-horsementioning
confidence: 99%